ความต้องการรับบริการวิชาการสาขาวิชาดนตรีมหาวิทยาลัยราชภัฏมหาสารคาม ของหน่วยงานราชการในจังหวัดมหาสารคาม Maha Sarakham Provincial Organizations Need on Music Academic Service From The Music Department Rajabhat Mahasarakham University - เชื่อมกลาง, อัครวัตร (Chophayom Journal, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อสารวจความต้องการในการรับบริการวิชาการแกสังคมจากหลักสูตรสาขาวิชาดนตรีมหาวิทยาลัยราชภัฏมหาสารคาม ของหน่วยงานราชการในจังหวัดมหาสารคาม ประชากรและกลุ่มตัวอย่าง คือ บุคลากรหน่วยงานราชการในจังหวัดมหาสารคาม โดยแบ่งเป็นหน่วยงานด้านการปกครอง ด้านการศึกษา ด้านสาธารณสุข และด้านอื่นๆ รวม 316 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามความต้องการรับบริการวิชาการ วิเคราะห์ข้อมูลโดยการหาค่าแจกแจงความถี่ ค่าร้อยละ โดยใช้โปรแกรมสาเร็จรูป SPSS สรุปผลการวิจัยไดดังนี้ ในภาพรวมหน่วยงานราชการต้องการรับบริการวิชาการด้านการจัดฝึกอบรมสัมมนามากที่สุด รองลงมาคือ ด้านกิจกรรมวงดนตรี รองลงมาคือ ด้านการเรียนการสอน และด้านการค้นคว้า วิจัย แหล่งอ้างอิง มีความต้องการรับบริการน้อยที่สุด ข้อเสนอแนะตามบริบทของหน่วยงาน พบว่า หน่วยงานด้านการปกครองต้องการให้สาขาวิชาดนตรี ร่วมทากิจกรรมกับท้องถิ่น เพื่อดึงดูดความสนใจให้คนเข้าร่วมกิจกรรมต่างๆ ของหน่วยงาน และยินดีให้ความร่วมมือกับสาขาดนตรี ในการทากิจกรรมภายในมหาวิทยาลัย หน่วยงานด้านการศึกษา ต้องการวิทยากรหรือผู้สอนดนตรี โดยเฉพาะนักศึกษาฝึกสอน และต้องการผู้ฝึกซ้อมวงดนตรีต่างๆ เช่น วงโยธวาทิต วงดนตรีพื้นบ้าน เป็นต้น เนื่องด้วยดนตรีมีเครื่องดนตรี แต่ขาดบุคลากรในการให้ความรู้ ด้านสาธารณสุข ต้องการให้มีการจัดกิจกรรมดนตรีสาหรับผู้ป่วยและบุคลากรที่ปฏิบัติหน้าที่ในหน่วยงาน โดยเฉพาะกิจกรรมดนตรีบาบัดเป็นกิจกรรมที่เป็นที่ต้องการสาหรับผู้ป่วย และดนตรีสาหรับผู้สูงอายุ หน่วยงานด้านอื่นๆ ต้องการวงดนตรี สาหรับทากิจกรรมต่างๆ ของหน่วยงาน เช่น งานกีฬา งานเทศกาลต่างๆ เป็นต้น คำสำคัญ : ความต้องการ, สาขาวิชาดนตรี, บริการวิชาการ ABSTRACT The current study was conducted with the purpose to investigate needs of governmental organizations in Maha Sarakham Province, Thailand, in Rajabhat Maha Sarakham University Music Curriculum academic services. The population and sampling of the study was personnel in Maha Sarakham province including 316 officials in education, health care, and other organizations. The research instruments were a questionnaire designed to investigate needs in academic services. The data were analyzed by frequency and percentage using the SPSS program. The result of the study showed that the overview need of the governmental organizations were the need in seminars and workshops, music activities, music instruction, and research respectively. The research instruments were a questionnaire designed to investigate needs in academic services. The data were analyzed by frequency and percentage using the SPSS program. The result of the study showed that the overview need of the governmental organizations were the need in seminars and workshops, music activities, music instruction, and research respectively. Moreover, the participants in education suggested that the organization pleased to welcome several activities from the curriculum such as marching bands and local music bands. This was because the organizations were ready in terms of instruments, but they lacked academic instruction. In the health care organization, it was reported that there were needs in music activity in treatment and personnel working in the organization. Especially, music therapy was reported to be demanded in treatment for patients and elders. In other organization, the needs of academic service were reported as a supported activity in sport competitions and festival ceremonies. Keywords : Need Analysis, Music Department, Academic Service.